' Ulama', Politics, and the Public Sphere : An Egyptian Perspective - Hatina, Meir (Book collections on Project MUSE., 2010)
The present study, however, returns to an earlier period in history and shows that such vitality is not new. Its roots go back to the late nineteenth century, an accelerated period of state building and national cohesion. The sustained efforts of the `ulama' to restrain the nationalist/modernist impetus, the study further argues, facilitated a more convenient climate for dissident Islamic movements to further their cause. --Book Jacket.